CONTEXTUALIZATION OF DEMING AND CROSBY'S THEORIES IN IMPROVING EDUCATIONAL INSTITUTIONS - Ahmadi, Idris; Amin, Muhammad Fathul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is a figure thinking study focused on two quality thinkers, Deming and Crosby. Using the Library Reseach research method presented in the form of argumentative approaches and descriptive analysis. The 14 quality points expressed by Deming and Crosby are interesting for further investigation, Deming emphasizes the scope of the concept and the theory of quality management, while Crosbye focuses on the construction of the components of the quality management as well as the details of its implementation. In this article, the author offers the theoretical concepts and contextualization of quality management Deming and Crosby in improving the quality of education with the concept of